Work, Unity, and Aesthetic Plenitude in La Peste by Albert Camus - Carmen Romero Sánchez-Palencia (Universitas Sanata Dharma, 2020)
Albert Camus, and his work, is the perfect example of achievement through personal growth, with a unitary conception of the individual and their relationship with the world and with others. In confronting the immediate, the author offers repose; in the face of the absurd, revolt, and in the face of a meaninglessness he proposes love. His task is advance, our advance, climbing a long ladder that we may also descend, although transformed, no longer as we were the first time. This project will analyse the book La Peste / The Plague, relating it and the ideas here expressed with the concept of work. Work being understood as something beyond mere occupation, or way of making a living, but the endeavours of the subject as an essential component of life. This becomes evident when one seeks to grow fully, in harmony with humanity as embodied by Camus’ characters in a situation of collective emergency, in a city in the grip of the plague. The result is a hymn of hope, of momentary triumph not without repeated stumbles, recalling again and again what we are and what we can become. Just as in our own lives, the nebulous is the constant companion of victory, which is never entirely complete.